Establishment of tissue culture for selected medicinal curcuma spp - Yusuf, N.A.; Khalid, Norzulaani; Ibrahim, H. (Faculty of Science, University of Malaya, 2007)
The effect of cytokinin on shoot multiplication was studied to establish a micropropagation protocol. An average of eight shoots per explant was produced within four weeks on agar solidified Murashige and Skoog medium supplemented with 3.0 sucrose. The optimum concentrations of BAP for in vitro multiplications were 3.0 mg/1 for all species studied. Plantlets were rooted and successfully acclimatized to field conditions. The field performances between in vitro and in vivo plants were compared. The result showed very significantly that tissue culture derived plants were better than the ones that were conventionally propagated.